2021
DOI: 10.36953/ecj.2021.22313
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of IPM module against major insect pests of green gram, Vigna radiata (L.) Wilczek in lower Gangetic plains of West Bengal

Abstract: An experiment was carried out to evaluate the efficacy of integrated management practices over farmers’ practices against insect pest complex of green gram (Vigna radiata L. Wilczek) during kharif season in the ‘A-B’ Block Farm of Bidhan Chandra Krishi Viswavidyalaya in 2019. The results revealed that the incidence of all of the insect pests viz. whitefly, pulse aphid, jassid, flower thrips, gram pod borer, spotted pod borer, blue butterfly, plant bug and pod bug was recorded comparatively less in Integrated P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
4
0
0
Order By: Relevance
“…The findings of this experiment are in accordance with the outcomes ofMalik et al (2021) andBanerjee and Ray (2022) who reported the excellence of IPM module compared with Farmer's practice earlier. Findings of the present experiment have very close association with the findings of Gajendran…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The findings of this experiment are in accordance with the outcomes ofMalik et al (2021) andBanerjee and Ray (2022) who reported the excellence of IPM module compared with Farmer's practice earlier. Findings of the present experiment have very close association with the findings of Gajendran…”
supporting
confidence: 89%
“…Similar findings were also obtained by Sujatha and Bharpoda (2016) who reported the efficacy of thiamethoxam 25 WG (0.01%) in managing the sucking pests as evidenced in this study. Results of Malik et al (2021) are closely associated with the present outcomes as they reported higher efficacy of biorational insecticide Chlorantarniliprole in managing spotted pod borer infesting green gram from IPM module compared to the farmer's practice where it was not used.…”
Section: Comparative Study Of Module Based Strategy and Farmer's Prac...supporting
confidence: 74%
“…The findings of this experiment are in accordance with the outcomes ofMalik et al (2021) andBanerjee and Ray (2022) who reported the excellence of IPM module compared with Farmer's practice earlier. Findings of the present experiment have very close association with the findings of Gajendran…”
supporting
confidence: 89%
“…Similar findings were also obtained by Sujatha and Bharpoda (2016) who reported the efficacy of thiamethoxam 25 WG (0.01%) in managing the sucking pests as evidenced in this study. Results of Malik et al (2021) are closely associated with the present outcomes as they reported higher efficacy of biorational insecticide Chlorantarniliprole in managing spotted pod borer infesting green gram from IPM module compared to the farmer's practice where it was not used.…”
Section: Comparative Study Of Module Based Strategy and Farmer's Prac...supporting
confidence: 74%